Evaluación del comportamiento en poscosecha de zanahoria amarilla con 3 tiempos de hidrocooling, 2 atmósferas modificadas y 3 temperaturas de almacenamiento en el ceypsa Universidad Técnica de Cotopaxi provincia de Cotopaxi - Guanoluisa Guanopatín, Sylvia Carolina (2015)
This researching was performed in “Salache” neighborhood, Latacunga Canton, Cotopaxi Province. Its main objective was; To evaluate the postharvest behavior of the yellow carrot (Daucus carota) with three hydrocooling times, two modified atmospheres and three storage temperatures. The applied method was the experimental of plot design, devided twice (DP2VD), as the hypothetical and deductive and the applied techniques were the field study observation and data gathering which were fullfilled every 8 days. The main results of the research were, the best time of hydrocooling was the number 3 (25 min) (H3), the optimum temperature was number 1 (4° C) (T1), which helped keeping the most yellow carrot features for 56 days for human consumption; Further the modified atmosphere with the best results was the number 2 (trays with roll pack) (A2) as the hydrocooling and atmosphere kept the characteristics of specie at the same time. The best treatment interaction was Nº 6 (T1A2H3), for 56 days, which showed less weight loss, acidity and length and with this less incidence of diseases and pathologies. The researching contribution to the producer, is to give conservation alternatives and added value product (carrot) reducing the production losses so as to enhance the economic farmer status.